2018
DOI: 10.1007/s00018-018-2785-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the efficacy of cell penetrating peptide-based cancer vaccines

Abstract: Immunotherapies are increasingly used to treat cancer, with some outstanding results. Immunotherapy modalities include therapeutic vaccination to eliminate cancer cells through the activation of patient’s immune system against tumor-derived antigens. Nevertheless, the full potential of therapeutic vaccination has yet to be demonstrated clinically because many early generation vaccines elicited low-level immune responses targeting only few tumor antigens. Cell penetrating peptides (CPPs) are highly promising to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 82 publications
(111 reference statements)
2
34
0
4
Order By: Relevance
“…In general, CPPs were used to deliver antigenic peptides or proteins, induce adaptive immune responses and activate both CD8 + and CD4 + T cells [283]. For example, the EBV ZEBRA proteinderived CPPs (Z12, Z13, or Z14) linked to antigenic cargos (e.g.…”
Section: Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…In general, CPPs were used to deliver antigenic peptides or proteins, induce adaptive immune responses and activate both CD8 + and CD4 + T cells [283]. For example, the EBV ZEBRA proteinderived CPPs (Z12, Z13, or Z14) linked to antigenic cargos (e.g.…”
Section: Vaccinementioning
confidence: 99%
“…Increased antigen (Ag)-specific immune responses were also reported by linking other tumor antigens (e.g. carcinoembryonic antigen, TRP2, survivin, p53, HPV16 E7, MUC-1, or HER2/neu) to a CPP [283]. Wang et al demonstrated that the linkage of TRP2 Ag to CPPs could prolong antigen presentation by dendritic cells (DCs) [286].…”
Section: Vaccinementioning
confidence: 99%
“…The ability of a given substance to trigger an immune response is referred to as immunogenicity (6, 8). In a broader sense, immunogenicity refers to the activation of both sides of adaptive immunity: cellular response (mediated by cytotoxic cells) and humoral response (mediated by antibodies).…”
Section: Introductionmentioning
confidence: 99%
“…In a broader sense, immunogenicity refers to the activation of both sides of adaptive immunity: cellular response (mediated by cytotoxic cells) and humoral response (mediated by antibodies). The activation of T-cells is a decisive step in both cases (8, 9), and it will also be referred to as immunogenicity here. T-cells are a special type of lymphocyte that undergo a complex maturation and selection process, which makes them capable of recognizing “non-self” peptides (10).…”
Section: Introductionmentioning
confidence: 99%
“…The cell penetrating property of these peptides have been utilized to deliver antigenic peptide and proteins into any antigen presenting cell including DCs for the development of vaccine delivery systems [ 4 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. For this purpose, CPP peptides chemically conjugated to protein antigens or linear synthetic peptides of CPP fused in tandem with cytotoxic (Tc) or helper (Th) T cell epitopes have been used.…”
Section: Introductionmentioning
confidence: 99%